2016
DOI: 10.3855/jidc.7577
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transmission of multidrug-resistant Corynebacterium striatum among susceptible patients in a tertiary hospital in China

Abstract: Introduction: With increasing reports about Corynebacterium striatum, its potential pathogenicity and clinical significance are drawing more attention in recent years. Methodology: During a 14-month period, Corynebacterium striatum strains were routinely isolated in lower respiratory tract samples of the inpatients in a tertiary hospital in China, and the suspected isolates were identified with VITEK-2 ANC card and 16S rRNA sequencing technique, respectively. Pulsed-field gel electrophoresis (PFGE) was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…It is reported that C. striatum can colonize onto multiple environmental and bodily surfaces and could transmit within patients in specific wards [12,13]. Also, the multi-drug resistant C. striatum clones seemed to be with stronger adhesion abilities [14] , which was consistent with one of our previous study [15], which may partly explain the reason why C. striatum can rapidly transmit within hospital environment. Moreover, Souza C et al [16] reported that C. striatum could lead to the death of Caenorhabditis elegans, and virulence potential varied among different C. striatum clones.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is reported that C. striatum can colonize onto multiple environmental and bodily surfaces and could transmit within patients in specific wards [12,13]. Also, the multi-drug resistant C. striatum clones seemed to be with stronger adhesion abilities [14] , which was consistent with one of our previous study [15], which may partly explain the reason why C. striatum can rapidly transmit within hospital environment. Moreover, Souza C et al [16] reported that C. striatum could lead to the death of Caenorhabditis elegans, and virulence potential varied among different C. striatum clones.…”
Section: Introductionsupporting
confidence: 89%
“…In general, the whole genomic DNA chromosome of the C. striatum was extracted, and macrorestriction digestion (SwaI) and PFGE (CHEF-DR II apparatus; Bio-Rad, Hercules, CA, USA) were performed as previously reported [15]. Macrorestriction patterns were analysed using Dice coefficient with Bionumerics software (Applied Maths, Kortrijk, Belgium,Version 5.0).…”
Section: Pulsed-field Gel Electrophoresis (Pfge)mentioning
confidence: 99%
“…Corynebacterium striatum is frequently isolated from patients hospitalized long-term, treated with invasive procedures, and having underlying diseases such as COPD [12,13,19,20]. In this study, the most common underlying disease in patients was COPD, followed by cardiovascular diseases and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 78%
“…Alibi et al [23] detected 22 PFGE profile in 63 C. striatum strains from Tunisia and reported high clonal diversity among strains. Wang et al [19] reported that three epidemic clones were spread by PFGE in 82 C. striatum strains isolated from patients' respiratory samples between 2013 and 2014 in China. Wang et al [24] applied PFGE to 192 C. striatum isolated between 2017 and 2018, and also performed whole genome sequencing in 91 C. striatum isolates and reported that there was multiclonal spread within the hospital simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and identification of pathobiontic bacteria was attempted from clinical samples, that is, bronchoalveolar lavage fluid (BLF), endotracheal aspirates (ES), sputum, and blood [16]. The genetic relatedness of the resulting isolates was analysed using pulse-field gel electrophoresis (PFGE) [17][18][19][20][21][22], whole genome sequencing, and sequence comparisons (Supplemental Methods).…”
Section: Pathobiontic Bacterial Species Isolation and Genetic-relatedmentioning
confidence: 99%